2014
DOI: 10.1111/brv.12146
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of proline biosynthesis: enzymology, bioinformatics, genetics, and transcriptional regulation

Abstract: Proline is not only an essential component of proteins but it also has important roles in adaptation to osmotic and dehydration stresses, redox control, and apoptosis. Here, we review pathways of proline biosynthesis in the three domains of life. Pathway reconstruction from genome data for hundreds of eubacterial and dozens of archaeal and eukaryotic organisms revealed evolutionary conservation and variations of this pathway across different taxa. In the most prevalent pathway of proline synthesis, glutamate i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
161
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 185 publications
(172 citation statements)
references
References 247 publications
(345 reference statements)
9
161
0
2
Order By: Relevance
“…The promoter and 59 UTR region of the P5CS1 gene contains most conserved cis elements, which were predicted as potential TF binding sites (Supplemental Figs. S1 and S2;Fichman et al, 2015;Song et al, 2016). Besides the 59 regulatory region, introns have been reported to carry regulatory elements with capacity to enhance transcription in a number of genes (Lohmann et al, 2001;Casas-Mollano et al, 2006;Gallegos and Rose, 2015), including the high-affinity phosphate transporter AtPht1;4 (Karthikeyan et al, 2009).…”
Section: Phosphate Starvation Response Factors Identified By a Yeast mentioning
confidence: 99%
See 1 more Smart Citation
“…The promoter and 59 UTR region of the P5CS1 gene contains most conserved cis elements, which were predicted as potential TF binding sites (Supplemental Figs. S1 and S2;Fichman et al, 2015;Song et al, 2016). Besides the 59 regulatory region, introns have been reported to carry regulatory elements with capacity to enhance transcription in a number of genes (Lohmann et al, 2001;Casas-Mollano et al, 2006;Gallegos and Rose, 2015), including the high-affinity phosphate transporter AtPht1;4 (Karthikeyan et al, 2009).…”
Section: Phosphate Starvation Response Factors Identified By a Yeast mentioning
confidence: 99%
“…The P5CS1 promoter contains sequence motifs that are conserved in related Brassicaceae species and can be binding sites for basic Leu zipper (bZIP), myeloblastosis (MYB), c-Myc (MYC), APETALA2/Ethylene-responsive element binding protein (AP2/EREBP), C2H2 Zn finger protein (C2H2_Zn) type transcription factors (Supplemental Fig. S1; Fichman et al, 2015). A recent chromatin immunoprecipitation (ChIP)-seq study suggests that several ABA-regulated transcription factors (TFs) can bind to the promoter region of the P5CS1 gene (Supplemental Fig.…”
mentioning
confidence: 99%
“…Our results observed that only 24 out of 100 (24%) of putatively transformed grape plants with pBI121 contained the P5CS gene and were confirmed to be transgenic by PCR. In previous studies, researchers have attempted to focus on P5CS expression patterns in higher plants and they found increasing levels of constitutive transcript abundance compared with the genes VaP5CS (de Carvalho et al, 2013), OsP5CS (Igarashi et al, 1997), PvP5CS (Chen et al, 2009), JcP5CS (Wang et al, 2011), AtP5CS1 (Zhuang et al, 2011) and MsP5CS1 (Fichman et al, 2014). Induction of transcript expression of P5CS gene has also been reported in response to abiotic stresses (Neffar et al, 2011) and it was found to encourage proline synthesis and improved stress tolerance (Vendruscolo et al, 2007;Patade et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The action of proline varies among plant organs, for instance it has been found to help redistribute nitrogen to younger tissue in leaves and it also helps counter energy shortages in flowers (Zhang and Becker, 2015). A plant protecting him against the lethal effects of salinity by over accumulation of proline that may be resulting from salinity inducible uptake of exogenous proline confers (Fichman et al, 2014). Several studies have highlighted the possible mechanisms of proline accumulation under stress condition; 1-by restricting entrance of non-metabolisable ions such as sodium, transporting them to vacuoles and or excluding them from the cytosol and thus reducing their toxicity (Verbruggen and Hermans, 2008); 2-acting as a non-enzymatic osmoprotectant which suggests it could replace water at protein surfaces, in protein complexes or in membranes Hasegawa et al (2000); 3-acting as both an osmotic agent and a radical scavenger (Kishor and Sreenivasulu, 2014) and; 4-act to balance cell redox status and to buffer cytosolic pH (Maggio et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…6, Tables 1, 3). The amino acid proline is associated with environmental stresses Foolad 2007 andFichman et al, 2015). Plants engineered to accumulate proline exhibit the ability to tolerate salinity, oxidative and drought stress (Hong et al, 2000).…”
Section: Photosynthetic Pigmentsmentioning
confidence: 99%